Analyzing and Assessing a Library Collection Using Faculty Citations Via OpenAlex and R - Orner, Sylvia (Evidence Based Library and Information Practice, 2024)
Objective – Citation analysis is becoming a popular means of analyzing and assessing library collections due to its relatively unobtrusive nature and the growing accessibility of citation data. The primary goal of this study was to assess whether the library at the University of Scranton is successfully meeting the research needs of faculty based on analysis of faculty publication and citation data from OpenAlex’s application programming interface. Secondarily, this study analyzed faculty publication and citation patterns to help identify opportunities for the library to better support faculty in their research and publishing.Methods – This case study focused on a citation analysis of the University of Scranton’s faculty publications from 2013 to the present. Using OpenAlex and R computing language as non-proprietary sources of data and data analysis, faculty publications and citations were examined and compared to current library holdings.Results – Overall, 16,786 unique citations from 1,045 unique faculty publications were examined and compared to a list of current library holdings. Findings concluded that approximately 65% of citations were available through library holdings. Further analysis of faculty publication practices suggested that there are a growing number of faculty publishing open access which indicates that there may be additional opportunities to support faculty in this area.Conclusion – While this case study represented specific needs and use cases at the University of Scranton, the ultimate importance of this study is the process itself. The use of non-proprietary tools and data sources like OpenAlex and R create exciting new opportunities for others who wish to conduct similar studies at their own institutions without relying on proprietary tools and data sources or resorting to more labor-intensive methods.